ANALISIS MAKNA PADA PETUAH-PETUAH ADAT KEMANTEN KEMUNJILAN : ANALISIS PENDIDIKAN KARAKTER BUDAYA MASYARAKAT OSING BANYUWANGI - Faizatul Muniroh; Asngadi Rofiq (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to examine the meaning and values ​​of character education contained in the Kemanten Kemunjilan traditional advice in the Osing community in Banyuwangi. This tradition, which has been passed down from generation to generation, is considered a means to shape character through the symbols and philosophy contained in the traditional wedding procession. The method used in this study is a qualitative approach with descriptive-analytical techniques. Data were collected through in-depth interviews, participatory observation, documentation, and literature studies. The research informants consisted of traditional leaders, traditional healers, bridal couples, and community leaders who understand Osing cultural values. The results of the study show that the traditional advice in Kemanten Kemunjilan contains important values, such as responsibility, cooperation, steadfastness, spirituality, and family welfare. Each symbol in the ritual procession, such as agricultural tools, kitchen utensils, and other offerings, contains deep meaning related to household life. This study concludes that the Kemanten Kemunjilan tradition not only preserves Osing culture, but also functions as a medium for character education that instills moral and ethical values ​​for the next generation, as well as strengthening family relationships in Osing society